Analisis Faktor Kesulitan Belajar Siswa Dalam Meningkatkan Hasil Belajar Pada Mata Pelajaran Sosiologi Kelas XII IPS Di MA. Syarif Hidayatullah Pontianak - Rahmah, Rahmah (Jurnal Pendidikan Sosiologi dan Humaniora, 2013)
This research is to describe the difficulties of student learning to improve the achievement of sociology subject matter, the are: 1). the difficulties of student in learning sociology, 2). the effort of teacher to handle the difficulties of student dificulties, 3). how is the result of student to learning sociology. The instrument used in this research are observation, interview and documentation. The results show, 1). there were some internal and external factors of student barriers, 2). the effort had been done by teacher include to diagnose problems, 3). help student to motivate their habit in learning. Moreover teacher effort to diagnosisÂ  difficulties of learning more comprehend, do evaluation to determine of learning difficulties, 3). the achievement showed in mid test, there are student with less average of 70.Key Words: The Difficulties Learning Factor, Achrevement Of Study.Â